13C-NMR analysis of glucose metabolism during citric acid production by Aspergillus niger - Peksel, A; Torres, NV; Liu, J; Juneau, G; Kubicek, CP (SPRINGER-VERLAG, 2002)
The effect of glucose concentration on glycolytic metabolism under conditions of citric acid accumulation by Aspergillus niger was studied with C-13-labelled glucose. The results show that during cultivation at high glucose (14%, w/v), most of the label in citric acid is in C-2/C-4, and is thus due to the pyruvate carboxylase reaction. However, a significant portion is also present in C-1/C-5, whose origin is less clear but most likely due to reconsumption of glycerol and erythritol. Formation of trehalose and mannitol is high during the early phase of fermentation and declines thereafter. The early fermentation phase is further characterized by a high rate of anaplerosis from oxaloacetate to pyruvate, which also decreases with time. At low glucose concentrations (2%, w/v), which lead to a significantly reduced citric acid yield and formation rate, labelling of citrate in C-2/C-4 is decreased and C-1/C-5 labelling increased. Growth on 2% glucose is also characterized by an appreciable scrambling of mannitol and considerable backflux from mannitol to trehalose (indicating tight glycolytic control at the fructose-6-phosphate step) and an increased anaplerotic formation of pyruvate from oxaloacetate. These data indicate that cultivation on high sugar concentrations shifts control of glycolysis from fructose-6-phosphate to the glyceraldehyde-3-phosphate dehydrogenase step.
Keywords: ACCUMULATION; CYCLE; Biotechnology & Applied Microbiology